Pension Funds and the Impact of Switching Regulation on Long-Term Investment - Pedraza Morales, Alvaro Enrique; Fuentes, Olga; Searle, Pamela; Stewart, Fiona (World Bank, Washington, DC, 2017)
This paper looks at the impact of members' ability to switch pension fund provider and /or portfolio on the allocation of pension funds to long-term investments. The level of annual turnover in pension fund portfolios was compared with the amount of short-term investments (using government treasury bills and bank deposits as proxy). The investment regulations around switching and other market conduct were then considered. The paper finds that greater movements between pension fund providers and between portfolios is linked to increased holdings of short-term and more liquid assets. Switching appears to be driven by competition, market structure, and investment advice, and, unfortunately, frequently results in poor investment returns for members. The paper makes six recommends for regulators. First, use administrative controls to prevent fraudulent switching between pension providers. Second, provide clear performance and cost comparisons to inform members' choice of provider/fund and encourage informed decision making, which is beneficial for members and the system. Third, supervise and control advertising and marketing (including reporting of performance periods) carefully, to avoid switches based on misleading advice. Fourth, control financial incentives for sales agents, so that switching advice is given in members' interest and not for commercial gain. Fifth, concentrate issuance in government securities, to create more liquid instruments. And sixth, conduct further research on the concept of a central liquidity pool to manage unexpected outflows.